ChemInform Abstract: DES as a Green Solvent to Prepare 1, 2‐Bis‐organylseleno Alkenes. Scope and Limitations. Issue 14 (March 2016) - Lopes, Eric F.; Goncalves, Loren C.; Vinueza, Julio C. G.; Jacob, Raquel G.; Perin, Gelson; Santi, Claudio; Lenardao, Eder J.
Abstract: The use of choline chloride/urea as a deep eutectic solvent (DES) in the synthesis of vinyl selenides is described.